IADVL SIG pediatric dermatology (academy) recommendations on Hemangioma of Infancy (HOI) - Bhumesh K Katakam; Minu J Chiramel; Ram Gulati; Mrinal Gupta; Malathi Munisamy; P S S. Ranugha; K A Seetharam (Wolters Kluwer Medknow Publications, 2023)
Hemangioma of infancy (HOI) is a benign vascular proliferation. Though resolution is the norm, potential complications make an accurate diagnosis and early management of importance. The Indian association of dermatologists, venereologists and leprologists (IADVL) special interest group (SIG) paediatric dermatology in association with IADVL academy did an extensive analysis of the literature on the clinical features, diagnosis, and management of HOI published between 2010 and 2021. Online meetings were conducted from February 2021 to March 2022 to reach a consensus on these recommendations which are made from an Indian perspective.